Caracterização farmacêutica de nanocápsulas de timol e avaliação da permeação cutânea e da atividade repelente contra Aedes aegypti - Moraes, Anderson de Souza (2015)
Dengue is an infectious disease that may also happen in a severe form with hemorrhagic events. The etiological agent of the disease is an arbovirus wich is transmitted by the mosquito Aedes aegypti, the primary vector of the disease. The main actions to combat the disease are mosquito control and personal protection that can take place using repellents. Almost all repellents have DEET as active substance, which has use restrictions. In this context, thymol (monoterpene) has become a potential insect repellent against Ae. aegypti, and the use of technologies is essential to the viability of a repellent thymol based product. Given the above, the aim of this study was the preparation and pharmaceutical characterization of thymol nanocapsules and evaluation of skin permeation, in vitro cytotoxicity and mosquito repellence (Ae. aegypti). For this purpose, we developed and validated analytical method for identification and quantification of thymol by HPLC-PDA. Nanocapsules thymol (NCT - 1%) showed an active content of 85%. Continuing the characterization, NCT were analyzed for the mean diameter (D), polydispersity index (PDI), potential zeta (PZ), encapsulation efficiency, pH and product stability . Results shared showed an average diameter of approximately 150 nm, negative PZ (-27,83 ± 2,60), PDI less than 0.2 and an encapsulation efficiency of 98%. NCT and ethanolic solution of thymol were evaluated for release, permeation and retention of thymol through dialysis membrane or the porcine ear skin in a Franz diffusion cell model. NCT showed release control of thymol in relation to the ethanolic solution of thymol, which showed a maximal release of 53.8% of the dose within 24 hours of testing, higher than the amount released by the NCT (17.6%) indicating the decrease in permeability when nanoencapsulated. Cytotoxicity analysis of free and encapsulated thymol (50 to 100 ug / ml) in human keratinocytes by MTT assay showed cytotoxicity of free thymol - 100 ug / mL (% viable cells: 16.1 ± 3.2 ), which was virtually devoid with this encapsulation (% viable cells: 92.7 ± 31). Preliminary assessment of the repellent potential of NCT against Ae. aegypti showed that in human topical administration of the product promoted up to 67% repellency. The results suggest that standardized NCT has morphological and chemical characteristics of interest to a nanossystem, plus the potential repellent against Ae. aegypti mosquito.